The Massacres of Migrants in San Fernando and Cadereyta: Two Examples of Necropolitan Governmentality - Amarela Varela Huerta (Íconos)
The text addresses two emblematic massacres of migrants from contemporary Mexico, the San Fernando, Tamaulipas massacre in 2010, and the Cadereyta, Nuevo Leon massacre in 2012 as examples of a "necropolitan governmentality" of migrations in Mesoamerica. It is hypothesized that these massacres are, in addition to disputes over territorial control, crimes that with their performativity seek to exemplify the punishment for those who dare to disobey the laws of access and permanence in the North American territory (Mexico or United States of America). It is an analytical exercise that emphasizes the violence against migrants, which are essential scenarios to be understood in contemporary migratory studies.